(untitled) - Rabion, Alain; Panigada, Davide; Roy, Sebastien; Bigot, Antony; Tedrow, Jason S. (Comptes Rendus. Chimie)
Biocatalysis is widely regarded as a sustainable technology to innovate Active Pharmaceutical Ingredient (API) synthesis. Biotransformation is considered a unique technology in the drug manufacturing world to unlock synthetic routes to complex chiral motifs. Sanofi is accelerating the development of strong mindset and efficient capabilities in biocatalysis to foster API delivery and promote greener solutions for its synthetic processes.In this article, we will describe how Sanofi is building its internal biocatalytic capabilities in order to address new challenges related to sustainability and the growing complexity of its portfolio. The outcomes of recent studies will be presented demonstrating the successful implementation of the biocatalysis technology across early and late-stage development of our pipeline assets.